2013
DOI: 10.3897/zookeys.336.5139
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Porifera in the Mediterranean coralligenous accretions, with description of a new species

Abstract: Temperate reefs, built by multilayers of encrusting algae accumulated during hundreds to thousands of years, represent one of the most important habitats of the Mediterranean Sea. These bioconstructions are known as “coralligenous” and their spatial complexity allows the formation of heterogeneous microhabitats offering opportunities for a large number of small cryptic species hardly ever considered.Although sponges are the dominant animal taxon in the coralligenous rims with both insinuating and perforating s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 21 publications
2
59
0
1
Order By: Relevance
“…Our results are related to a small spatial scale, and a wider sample design could lead to different patterns (Andrew & Mapstone, 1987) and ratio between inner and outer sponges as evidenced for example in Bertolino et al (2013). In general, coralligenous assemblages can show a wide homogeneity at a large-scale, resulting in a lack of significant differences between separate locations (Piazzi et al, 2004), while at small scale, a high heterogeneity is always evident, limiting the definition of a standardized monitoring protocol valid at Mediterranean level (Zapata et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results are related to a small spatial scale, and a wider sample design could lead to different patterns (Andrew & Mapstone, 1987) and ratio between inner and outer sponges as evidenced for example in Bertolino et al (2013). In general, coralligenous assemblages can show a wide homogeneity at a large-scale, resulting in a lack of significant differences between separate locations (Piazzi et al, 2004), while at small scale, a high heterogeneity is always evident, limiting the definition of a standardized monitoring protocol valid at Mediterranean level (Zapata et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Just like the coral reefs, also for coralligenous accretions, it is possible to hypothesise that cryptic fauna may play a crucial functional role. The holes and crevices of this biogenic structure support a complex community dominated by suspension feeders (sponges, hydrozoans, tunicates, bryozoans, serpulids, mollusks), with sponges representing the most abundant taxon (Ballesteros, 2006;Bertolino et al, 2013). Bertolino et al (2013), sectioning big coralligenous blocks into slices identified the presence of 27 exclusively endolithic species giving an idea of the richness of this group inside the coralligenous substrata.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is one of the most important coastal ecosystems of the Mediterranean Sea for distribution, biodiversity, productivity and role in the CO 2 cycle (Bertolino et al 2013, Martin et al 2014, Casas-Guell et al 2015. Coralligenous habitat is considered sensitive to human activities (Piazzi et al 2012, Cánovas Molina et al 2016) and has been included in the protection programme of European legislation (e.g.…”
Section: Introductionmentioning
confidence: 99%